Language Style in the Advertisements Broadcast in Cassanova Bali Radio - Puspa Priani, Dewa Ayu Made Nadya; Sari Dewi, A.A. Sagung Shanti; Budiasa, I Gede (Humanis, 2019)
The study entitled Language Style in the Advertisements Broadcast in Cassanova Bali Radio are aimed to identify the types of language styles used and to analyze the linguistic features that are applied in Cassanova Bali radio advertisements. The data of this study was taken from six advertisement scripts on Cassanova Bali radio that broadcast from August 1 st until August 30 th 2017. These data were collected by using documentation method and analyzed by using qualitative method based on the theory proposed by Holmes (1992) and Grey (2008). After analyzing the data, vernacular language is the most common language style used by Cassanova Bali radio and found in five advertisements (17 sentences), meanwhile the standard language is rarely used by Cassanova Bali radio and only found in one advertisement (3 sentences). It was also found that Cassanova Bali radio used five linguistic features to attract more consumers and the most common feature is familiar language (24 words), followed by use of imperative (15 words), hyperbole (6 words), repetition (3 words) and simple vocabulary (3 words).